Recent Progress on the Scanning Tunneling Microscopy and Spectroscopy Study of Semiconductor Heterojunctions. Issue 50 (1st August 2021) - Peng, Wenbing; Wang, Haolin; Lu, Hui; Yin, Lei; Wang, Yue; Grandidier, Bruno; Yang, Deren; Pi, Xiaodong
Abstract: The band alignment, interface states, interface coupling, and carrier transport of semiconductor heterojunctions (SHs) need to be well understood for the design and fabrication of various important semiconductor structures and devices. Scanning tunneling microscopy (STM) with high spatial resolution and scanning tunneling spectroscopy (STS) with high energy resolution are significantly contributing to the understanding on the important properties of SHs. In this work, the recent progress on the use of STM and STS to study lateral, vertical and bulk SHs is reviewed. The spatial structures of SHs with atomically flat surface have been examined with STM. The electronic band structures (e. g., the band offset, interface state, and space charge region) of SHs are measured with STS. Combined with the spatial structures and the tunneling spectra features, the mechanism for the carrier transport in the SH may be proposed. Abstract : Scanning tunneling microscopy and spectroscopy (STM/STS) are critical to research on semiconductor heterojunctions (SHs). Recent progress on the study of SHs by using STM/STS is reviewed. Beginning with the basics of STM/STS, both common and advanced STM/STS methods are introduced for research on SHs. Three types of SHs (i.e., lateral, vertical and bulk SHs) investigated with STM/STS are concerned.